Trichogramma piceum Dyurich (Hymenoptera Trichogrammatidae), new species for Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Trichogramma piceum Dyurich (Hymenoptera Trichogrammatidae) is recorded for the first time from ltaly. The parasitoid has been reared from egg-mass of Hyphantria cunea Drury (Lepidoptera Arctiidae) in Northern ltaly. The taxonomic characteristics of T. piceum are described, assigning the species to the flandersi group.
Keywords: Egg-parasitoid; Hyphantria cunea; flandersi